pengukuran aktivitas spesifik 226Ra, 232Th dan 40K dalam air sungai Hulu Gadut menggunakan spektrometer gamma - Yudayanti, Ila Yudayanti; Milvita, Dian; Kusdiana, Kusdiana (Universitas Andalas, 2025)
Research has been carried out on determining the specific activity 226Ra, 232Th and 40K in river water using gamma spectrometer. This study aims to determine the specific activities in river water hulu gadut, which were then reviewed based on the PERKA BAPETEN No. 9 of 2009. The samples were collected from 3 location, then were prepared by steamed and covered for 30 days, then measured using gamma spectrometer for 17 hours. The results of measurement of specific activities that exist 226Ra is (0,47±0,36) Bq/Kg, at 232Th is (2,15±0,36) Bq/Kg. and 40K is (0,43±0,38) Bq/Kg. Based on the head of PERKA BAPETEN regulation No. 9/2009, the specific activity of radionuclide in river water Hulu Gadut is currently below the limit which are 1000 Bq/kg for 226Ra, 232Th and for 40K 10000 Bq/kg. Based on the data obtained it was concluded that, river water Hulu Gadut is still safe and meets the requirements of quality standards.